Pengaruh Self Efficacy Terhadap Kemampuan Pemecahan Masalah Matematis Siswa di Kelas VII MTsN 6 Agam Tahun Pelajaran 2024/2025 - Siti Halimah; Isnaniah Isnaniah; Darul Darul; Rusdi Rusdi (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This research is motivated by the problems found in the seventh-grade class at MTsN 6 Agam, where students' mathematical problem-solving abilities are still relatively lacking, with many students scoring below 40 in problem-solving with a percentage ranging from 33%-44%, categorized as low. The low problem-solving abilities of the students are suspected to be influenced by one factor, namely Self Efficacy.It was found by the researcher during the observation that students easily give up and are unwilling to try to complete tasks, indicating a lack of self-efficacy among the students.The purpose of this research is to determine the effect of self-efficacy on mathematical problem-solving abilities.The population in this study is the seventh-grade students of MTsN 6 Agam for the 2024/2025 academic year.The research method used is quantitative research employing the ex post facto type of research.The sample was randomly taken from 20% of each class VII at MTsN 6 Agam, resulting in 51 students.The instruments used were the self-efficacy questionnaire and mathematical problem-solving ability test questions.Based on the analysis of the research data, it was found that there is a significant influence of self-efficacy on students' mathematical problem-solving abilities.This is evidenced by the hypothesis test results with a t_value of 17.968 and a t_table of 2.009, thus t_value > t_table at a confidence level of α = 0.05, which means there is a significant influence of self-efficacy on students' mathematical problem-solving abilities.without any reference or formula.